Hypothalamic GH Deficiency and gelastic seizures in a 10-year-old girl with MELAS - Matsuzaki, M; Izumi, T; Ebato, K; Suzuki, H; Shishikura, K; Osawa, M; Fukuyama, Y; Shimizu, N (No to hattatsu, 1991)
A case of mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes, in which a pituitary growth hormone (GH) secretion deficiency of hypothalamic origin was revealed through neuro-endocrinological examinations, was described. The case was a 10-year-old girl, who had been suffering from generalized tonic seizures since age 5, four episodes of alternating hemiplegia since age 6, stunted growth since age 7, and simple partial motor seizures as well as gelastic seizures since age 8. Marked elevation of lactate and pyruvate in both serum and CSF, abundant ragged red fibers in biopsied muscle, and low density areas in the left occipital lobe and bilateral globus pallidus in addition to diffuse brain atrophy on CT scan and MRI of the head were demonstrated, although the activities of muscle enzymes complex I-IV were within normal ranges. Pituitary GH secretion was deficient under the loadings with insulin, L-DOPA, sleep, and a single growth hormone releasing factor (GRF) administration, but normal GH response was registered under the repetitive stimulation with GRF. Activities of other hormonal axes were normal. It is likely that short stature commonly observed in MELAS patients is due to hypothalamic dysfunction, which might be brought out by chronic ischemia and energy deficiency of the diencephalon based upon mitochondrial abnormality of that region. It is likely that gelastic seizure in this case is due to hypothalamic dysfunction.